1909 Wash. Sess. Laws 972-73, ch. 249, § 265 - (:unkn) unknown (My University, 1909)
Prohibited manufacturing, selling, disposing of, or possessing any slung-shot, sand club, or metal knuckles. Also prohibited the concealed carry of any dagger, dirk, knife, pistol, or other dangerous weapon. Prohibited use of suppressors. Punishable as a gross misdemeanor.
Keywords: CARRY - CONCEALED; SUPPRESSORS; TRANSFER, MANUFACTURE & POSSESSION; TRANSFER, MANUFACTURE & POSSESSION - NON-GUN ARMS